2009
DOI: 10.21704/rea.v8i1-2.382
|View full text |Cite
|
Sign up to set email alerts
|

Determinación De La Flora Polinífera Del Valle De Oxapampa (Pasco-Perú) en Base a Estudios Palinológicos

Abstract: Se realizó un inventario florístico para obtener un herbario y una palinoteca de referencia, las muestras de polen corbicular se obtuvieron a través de trampas caza-polen. Las muestras de polen corbicular fueron separadas en grupos de acuerdo al color de los acúmulos de polen, realizándose cálculos de frecuencia. Las muestras de flora de referencia y polen corbicular fueron acetolizadas y luego analizadas por microscopia para la identificación de los tipos polínicos o taxa, correlacionándose el color de los ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…The CEs of propolis with the largest zones of inhibition were those from apiaries in Chontabamba, Saylla, Yura, and Oxapampa, with the last being widely studied and showing similar effects in previous studies ( Alemán et al ., 2018 ; Eguizábal & Nakata, 2014 ; Tovalino & Contreras, 2010 ). The boundless vegetation of the Oxapampa valley, where species such as Dictyocaryum lamarckianum (palm tree), Juglans neotropica (Andean walnut), Cyrtocymura scorpioides , Vernonanthura patens ( Kunth), Baccharis latifolia , Cecropia spp., Inga spp., and Pinus tecunumanii (timber tree), combined with the tropical climate of this area ( Muñoz & Del Pilar, 2015 ), offer a variety of active components that are transported by bees to their hives in the form of propolis ( Fernández-Calderón et al ., 2020 ; Okińczyc et al ., 2020 ; Rivera & Mesía, 2009 ). This variety enhances their biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…The CEs of propolis with the largest zones of inhibition were those from apiaries in Chontabamba, Saylla, Yura, and Oxapampa, with the last being widely studied and showing similar effects in previous studies ( Alemán et al ., 2018 ; Eguizábal & Nakata, 2014 ; Tovalino & Contreras, 2010 ). The boundless vegetation of the Oxapampa valley, where species such as Dictyocaryum lamarckianum (palm tree), Juglans neotropica (Andean walnut), Cyrtocymura scorpioides , Vernonanthura patens ( Kunth), Baccharis latifolia , Cecropia spp., Inga spp., and Pinus tecunumanii (timber tree), combined with the tropical climate of this area ( Muñoz & Del Pilar, 2015 ), offer a variety of active components that are transported by bees to their hives in the form of propolis ( Fernández-Calderón et al ., 2020 ; Okińczyc et al ., 2020 ; Rivera & Mesía, 2009 ). This variety enhances their biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between bees and floral resources is analyzed through palynological studies of pollen loads; thus, the plants that contribute to the diet of bees can be identified (Basilio 2000; Sayas Rivera and Huamán Mesía 2009). Indeed, the floral pollen sources of a region can be characterized to determine the botanical or geographical origin of honey and pollen loads (Andrada 2003; Forcone et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several works have analyzed the pollen resources used by A. mellifera in South America (Carpes et al 2009; De Novais et al 2009; Sayas Rivera and Huamán Mesía 2009; Chamorro-García et al 2013; Montenegro et al 2013; Hilgert Moreira et al 2014; Salamanca et al 2014; Negri et al 2018; Alves and Santos 2019; Casas Restrepo et al 2021). In Argentina, studies have been conducted in the Pampa phytogeographic province (Telleria 1993), Parana River Delta (Basilio 2000), southwest of Córdoba (Faye et al 2002), different areas of the Espinal (Andrada 2003; Andrada and Tellería 2005), Monte region in La Pampa province (Nabb and Tamame 2007), Patagonia (Forcone et al 2011; Forcone and Ruppel 2012) and in the central region of the country (García Paoloni 2021).…”
Section: Introductionmentioning
confidence: 99%
“…El análisis de los recursos poliníferos utilizados por Apis mellifera ha sido abordado por diversos autores de Sudamérica (Sayas Rivera & Huamán Mesía, 2009;Chamorro-Garcia et al, 2013;Montenegro, Pizarro, Mejias, & Rodriguez, 2013;Salamanca, Mónica, Tangarife, & Casas, 2014). En Argentina se encuentran los trabajos de Tellería (1993); Basilio (2000); Faye, Planchelo, & Molineli (2002); Andrada (2003); Andrada & Tellería (2005); Nabb & Tamame (2007); Forcone et al, (2011); Forcone & Ruppel (2012) y para el noroeste argentino solo el reporte de Burgos, Sánchez, & Lupo (2015) para la región del Chaco Serrano de la provincia de Jujuy.…”
unclassified